SYSTEMATIC LITERATURE REVIEW MAPPING OF GLOBAL, REGIONAL AND LOCAL FINTECH ADOPTION FROM THE PERSPECTIVE OF SHARIA ECONOMICS - Fuadi; A. Hadi Arifin; Iskandar; Azharsyah Ibrahim (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to map global, regional, and local trends in Financial Technology (FinTech) adoption from the perspective of Islamic economics through a Systematic Literature Review (SLR). The review examines the development of FinTech, particularly the integration of Artificial Intelligence (AI), open banking, RegTech, and digital financial services in the financial and banking industries worldwide and in Indonesia. The findings indicate that FinTech adoption has significantly transformed the financial sector by improving operational efficiency, enhancing customer experience, strengthening fraud detection, and expanding financial inclusion. At the global level, the rapid growth of open banking and AI-driven financial services reflects an increasing shift toward digital financial ecosystems. In Indonesia, FinTech adoption has accelerated digital transformation in banking and financial institutions, contributing to improved service quality and operational effectiveness. However, challenges related to cybersecurity, data privacy, ethical concerns, regulatory compliance, and systemic risks remain critical issues. From the perspective of Islamic economics, particularly the concept of maslahah mursalah, the literature suggests that Sharia FinTech can provide substantial benefits by promoting financial accessibility, efficiency, transparency, and economic welfare while maintaining compliance with Islamic principles. The study concludes that FinTech adoption generally supports the objectives of maqashid shariah by facilitating economic empowerment and public welfare, provided that technological innovation is accompanied by robust governance, cybersecurity measures, transparency, and regulatory oversight.